2013
DOI: 10.1080/15459624.2013.818234
|View full text |Cite
|
Sign up to set email alerts
|

Control of Airborne and Liquid-borne Fungal and Pet Allergens Using Microwave Irradiation

Abstract: In this study, the dog, cat allergens (Can f 1 and Fel d 1) and fungal allergens (Alt a 1 and Asp f 1) were aerosolized and exposed to the microwave irradiation (2450 MHz) at different output powers for up to 2 min. The allergen bioaerosols were collected by a BioSampler, and analyzed using enzyme-linked immunosorbent assay (ELISA). Control and microwave-irradiated Asp f 1 allergens were also tested with IgEs in human blood sera samples. For airborne Asp f 1 and Alt a 1 allergens, the allergenicity was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
1
15
1
Order By: Relevance
“…The inactivation performance of E. coli. bioaerosol, in this study, can reach 4-log, which is more efficient than that of waterborne exposure to MW irradiation (1-log) under similar experimental conditions [9]. Some other literatures reported higher inactivation performance in liquid phase using longer exposure time (several minutes or hours) and larger input energy [32].…”
Section: Bioaerosol Inactivation Performance By Mw Irradiationsupporting
confidence: 64%
See 1 more Smart Citation
“…The inactivation performance of E. coli. bioaerosol, in this study, can reach 4-log, which is more efficient than that of waterborne exposure to MW irradiation (1-log) under similar experimental conditions [9]. Some other literatures reported higher inactivation performance in liquid phase using longer exposure time (several minutes or hours) and larger input energy [32].…”
Section: Bioaerosol Inactivation Performance By Mw Irradiationsupporting
confidence: 64%
“…Many studies have utilized MWs to inactivate microorganisms in liquids [5], solids [6], and food [7]. Only a few studies on airborne microbes have been conducted [8,9].· Hamid et al reported preliminary results of MW on airborne fungi, yeast and bacteria in food processing plants [10]. Zhang et al utilized microwave assisted nanofibrous air filter to disinfect airborne E. coli cells and B. subtilis endospores [11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the required energies for 1-log inactivation were calculated as 2.3 J per loginactivation and 116.9 J per log-inactivation for airborne and waterborne bacteria, respectively. Therefore, the results demonstrated the superior energy efficacy for airborne microbes inactivation compared with waterborne microbes (Plazas-Tuttle et al, 2017;Wu & Yao, 2013). (Fig.…”
Section: Energy Efficiency and Utilization Pathwaymentioning
confidence: 88%
“…In the electromagnetic field, photons carrying electromagnetic radiant energy are absorbed to inactivate the microorganism (Wu & Yao, 2013;Wu & Yao, 2014). Herein, the detailed derivation process of the relationship between the microbial inactivation and absorbed energy is shown in SI 4(Support Information).…”
Section: Model For E Coli Inactivation Performancementioning
confidence: 99%
See 1 more Smart Citation